Social inequality - Warwick-Booth, Louise (Los Angeles Sage, 2013)
A student-friendly introduction to a popular subject that's taught across the social sciences. Critical, global, and totally student-focused.
What is social inequality? -- Social divisions and inequality : an overview -- Social divisions and inequality : social class -- Social divisions and inequality : gender -- Social divisions and inequality : ethnicity -- Globalization and the global dimensions of inequality -- The global social policy arena and inequality -- Social policy and its relationship to inequality : facilitator or potential solution? -- Solutions to inequality : how do we create a more equal global society?
Includes bibliographical references (pages [208]-229) and index.
Keywords: Equality